Zukunftsorientierte Entwicklung von Webseiten für Smartwatches nach aktuellen Standards - Kevin Brandao da Graca (2022)
The first smartphone with a full-featured browser was released on 09 November 2007 in Europe. For developers, this was the starting point for dealing with the development of mobile websites. Several years have passed since then and mobile device development has become routine. Terms like responsive design or mobile first are no longer unknown for web developers. This bachelor thesis deals with the future of mobile web development. The focus is mainly on the development of websites for smartwatches. Developing a website involves different phases. The thesis begins with a market and behavioral analysis to show which devices are currently in focus of developers and how these devices are different from smartwatches. It then examines the current web standards used for mobile web development. In the main part of the work, a web application is developed as a prototype. This prototype should contain different components of a website and be optimized for a smartwatch. The finished prototype will be evaluated and the methods used in the development will be described in the final part of the thesis.